Electronic Data Innovation Enhances Synergy Among Surakarta’s Regional Apparatus - Wedhana, Muhamad Edwin Zulfikar Atmani; Santoso, R. Slamet; Lituhayu, Dyah; Yuningsih, Tri (Journal of Transformative Governance and Social Justice, 2025)
This article analyzes the role of e-Tanov in fostering innovation synergy in the Surakarta City Government. In 2023, the e-Tanov application was implemented replacing the previous data collection method for innovation, which used to rely on Google Drive. With the implementation of e-Tanov, the number of innovations submitted surged significantly from 25 innovations in 2022 to150 innovations in 2024. Not only does this platform accelerate the management and evaluation of innovations, but it also enhances communication between regional apparatus and transparency, and makes it easier for the public to participate in submitting innovative ideas. The research also identified assessment criteria for regional innovations, such as social impact, sustainability and cost-effectiveness. In addition to this, the role of Badan Riset dan Inovasi Daerah (BRIDA) is essential in providing technical support and outreach to the regional apparatus, ensuring that the innovations produced are relevant to public needs. These findings suggest that e-Tanov increases not only the quantity of innovations, but also their quality, achieved through enhanced collaboration between various stakeholders. Therefore, it is expected that e-Tanov could serve as a model for other regions in implementing an effective and responsive innovation system, and encourage wider public participation in regional development